Principles of politics and Philippine government with the 1987 constitution - De Guzman, Rowena R.; Borras, Irene; Diego, Arnel Aviles; Olegario, Ma. Lourdes; Paras, Armando (Tarlac : HisGoPhil Publishing House, Inc., 2014)
This book is a product of combined efforts of the Philippine Government and new constitution professors for the past years.
1. Preface -- 2. Introduction -- 3. Concept of the state -- 4. The Machinery of the state -- 5. The Philippine Government : Branches of the Government ; Philippine Government in various periods -- 6. Political Parties -- 7. Citizenship -- 8. Local Government -- 9. Presidents of the thirds and fourth republic -- 10. The 1987 Philippine Constitution.
Includes bibliographical references.
Keywords: PHILIPPINE -- CONSTITUTION